The CBC “Ventures in Citizenship” Broadcast of 9 November 1938 (Kristallnacht) - Neary, Peter (Canadian Jewish Studies / Études juives canadiennes, 2002)
By coincidence, on the evening of 9 November 1938, Kristallnacht, the Canadian Broadcasting Corporation broadcast from Winnipeg, as part of its “Ventures in Citizenship” series, a programme celebrating the contributions of Jews to Canadian life. “Ventures in Citizenship” was the brainchild of Robert England, a prominent Great War veteran and writer on Canadian ethnic diversity, who was alarmed by the rise of Nazi Germany and sought to promote good inter-group relations in Canada and to prepare for the stresses of war. The broadcast highlighted the career of Lieutenant Myer Tutzer Cohen, who was killed in action in November 1917 and was awarded the Military Cross.